SERAPAN BAHASA ARAB DALAM PEMBERIAN NAMA PADA MASYARAKAT INDONESIA; KAJIAN MORFOSEMANTIK - Wulandari, Nawang; Nurkholis, Nurkholis; Faliandra Tanjung, Muhammad Ridho (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2022)
This research discusses the morpho-semantics of Arabic uptake words in naming Indonesian society, a study that examines Arabic loanwords into Indonesian. This type of research is qualitative descriptive. The purpose of this study is to find out the naming of Indonesian people using Arabic based on morphological and semantic studies based on categories on the word and its meaning. The results showed that the uptake of Arabic in naming Indonesian people morphologically comes from the class of words, namely nouns, verbs, adjectiva and numeralia.